1960
DOI: 10.1111/j.1469-8137.1960.tb06215.x
|View full text |Cite
|
Sign up to set email alerts
|

SOME ASPECTS OF THE DEVELOPMENTAL ANATOMY OF THE‘LONG’SHOOT IN LARIX DECIDUA MILL., WITH PARTICULAR REFERENCE TO SEASONAL PERIODICITY*

Abstract: Summary A description is given of the structure and behaviour of the terminal bud of the ‘long’ shoot in Larix decidua Mill, throughout the yearly growth cycle. Within the bud two regions of the new growth, the ‘axial’ and the ‘fascicular’, may be recognized. The capacity of a bud to grow into a ‘long’ shoot depends on the presence within it of the ‘axial’ portion, and is thus determined in the season prior to the opening of the bud. Weaker branches of the tree bear smaller terminal buds in which the ‘axial’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1964
1964
1988
1988

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This does not allow for neoformed leaf production, which is well established in Larix (Mitchell 1965;Kozlowski 1967, 1970;Fujimoto 1978;Owens and Molder 1979;Remphrey and Powell 1984b). Later, however, when writing of the most vigorous type of terminal bud, Frampton (1960) Frampton also drew for the "end of July" a longitudinal section of what appears to be a recently formed terminal bud. In terms of the current study and observations of L. decidua (G. R. Powell, unpublished data), Frampton's buds were far from "the most vigorous type", the shoots used were relatively weak and the descriptions contain inconsistencies.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…This does not allow for neoformed leaf production, which is well established in Larix (Mitchell 1965;Kozlowski 1967, 1970;Fujimoto 1978;Owens and Molder 1979;Remphrey and Powell 1984b). Later, however, when writing of the most vigorous type of terminal bud, Frampton (1960) Frampton also drew for the "end of July" a longitudinal section of what appears to be a recently formed terminal bud. In terms of the current study and observations of L. decidua (G. R. Powell, unpublished data), Frampton's buds were far from "the most vigorous type", the shoots used were relatively weak and the descriptions contain inconsistencies.…”
Section: Discussionmentioning
confidence: 85%
“…The timing of terminal-bud formation evident from dissections in the current study must be contrasted with the timing indicated from sectioning for L. occidentalis by Owens and Molder (1979), and to some extent from investigation of L. decidua by Frampton (1960). Owens and Molder (1979) found bud-scale formation to occur during May starting at about the time of bud burst and following a month-long period of leaf-primordium production (neoformation).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations